2003
DOI: 10.1007/bf03017852
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium potentiates neuromuscular blockade with cisatracurium during cardiac surgery

Abstract: P Pu ur rp po os se e: : Magnesium potentiates the effect of nondepolarizing neuromuscular blocking agents. It is used in cardiac anesthesia to prevent hypertension and arrhythmias. This study was performed to measure the interaction between magnesium and cisatracurium in cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
1
32
1
3
Order By: Relevance
“…An interaction between magnesium sulfate and the none-depolarizing neuromuscular blocking agents (NMBAs) has been documented for many years. This was also observed in patients undergoing cardiac surgery, where administration of magnesium sulfate results in a (30-35 min) prolongation of the neuromuscular blockade induced with intubating and maintenance doses of cisatracurium [14].…”
Section: Anesthetic Managementsmentioning
confidence: 63%
“…An interaction between magnesium sulfate and the none-depolarizing neuromuscular blocking agents (NMBAs) has been documented for many years. This was also observed in patients undergoing cardiac surgery, where administration of magnesium sulfate results in a (30-35 min) prolongation of the neuromuscular blockade induced with intubating and maintenance doses of cisatracurium [14].…”
Section: Anesthetic Managementsmentioning
confidence: 63%
“…These findings are consis-tent with those published by Kussman et al, who demonstrated increased durations of NMB in patients given magnesium sulphate before rocuronium 9 and with those published by Pinard et al, who showed prolonged NMB in cardiac surgery patients given magnesium sulphate and cisatracurium. 10 Lastly, it is interesting to note that the patients' postoperative serum calcium levels were low. Since calcium has the potential to reverse the effect of magnesium at the nerve terminal, low serum calcium may be an additional contributory factor.…”
Section: Conclusion : Nous Devons éViter D'administrer De Fortes Dosementioning
confidence: 99%
“…It is frequently used in anesthesia during repair surgery for patients with CHDs (Pinard et al, 2003;Mirinejad et al, 2007). However, the pharmacokinetics (PK) and pharmacodynamics (PD) of cisatracurium in patients with CHDs remain underexplored.…”
Section: Introductionmentioning
confidence: 99%